Pengaruh Volume Pemberian Air dan Jumlah Bibit per Lubang Tanam terhadap Pertumbuhan dan Hasil Tanaman Cabai Rawit (Capsicum frutescens L.) - Siska J Djalal; Wawan Pembengo; Nurdin (Transbahasa, 2026)
Bird’s eye chili is a type of plant with a very high market price. The low production of bird’s eye chili is influenced by factors such as water supply and seedling density, both of which affect plant growth and yield. This study aims to investigate the effects of water volume and seedling density per planting hole and their interaction on the growth and yield of bird’s eye chili. The study was conducted at the agricultural instrument standardization agency (BSIP) in Gorontalo Province from May to September 2024. The study used a factorial randomized bloch design (RBD). The first factor was water volume with three levels, and the second factor was seedling density with two levels. The parameters observed included plant height, leaf area, flowering age, number of fruits, and fruit wight. The data were analyzed using ANOVA followed by duncan’s multiple range test (DMRT) at a 5% significance level. Water volume significantly affected plant height, flowering age, and the weight of the first harvest fruit. In addition, No. interaction was found between water volume and seedling density for any of the observed parameters.